Pengaruh Model Pembelajaran ARCS (Attention, Relevance, Confidence, Satisfaction.) dan Motivasi Terhadap Hasil Belajar IPS Siswa Kelas V SD Negeri 75 Kota Bengkulu - Sukarno Sukarno; Salamah Salamah (Institut Agama Islam Negeri Bengkulu, 2019)
Abstract: Effect of ARCS Learning Model (Attention, Relevance, Confidence, Satisfaction) and Motivation on Social Studies Learning Outcomes of 5th Grade Students 75th State Elementary in Bengkulu City. This study aimed to determine the differences in student learning outcomes using the ARCS learning model with conventional learning models in class V of SD Negeri 75 Kota Bengkulu, differences in learning outcomes from groups of students with high learning motivation levels using the ARCS learning model with conventional learning models in class V SD Negeri 75 Kota Bengkulu, differences in learning outcomes from groups of students with low learning motivation levels using the ARCS learning model with conventional learning models in class V of SD Negeri 75 Kota Bengkulu, and interaction of learning models with motivation towards learning outcomes of fifth grade students at SD Negeri Kota Bengkulu. This study uses a quantitative approach with a type of quasi-experimental research. The subjects of this study were 75 elementary school students in the city of Bengkulu, totaling 62 students. Data collection is done by using tests and questionnaires with a research design using factorial 2X2. Data analysis techniques, using the